Local population genetic structure of the montane caddisfly Drusus discolor is driven by overland dispersal and spatial scaling. (28th October 2014) - Geismar, Jutta; Haase, Peter; Nowak, Carsten; Sauer, Jan; Pauls, Steffen U.
Summary Streams and rivers represent a special and complex case of dendritic networks, where comparable stretches of river habitat are isolated from each other by river stretches with different abiotic conditions as well as the terrestrial matrix. The capacity of stream insects for 'within‐network' (i.e. in‐stream) and 'out‐of‐network' (i.e. lateral overland) dispersal varies dramatically, making them good models for studying how these different dispersal modes affect community or population structure, and how landscape structure affects dispersal. In this study, we genotyped 1129 individuals of the montane caddisfly species Drusus discolor from 44 sampling sites for 20 microsatellite loci to assess local population structure and the importance of overland dispersal and gene flow in two central German highlands. Using species distribution models, we assessed whether suitability of the terrestrial habitat between streams influenced genetic structuring among sampling sites. Our results generally indicate high levels of overland dispersal at small and medium distances and show that the surrounding landscapes or catchment boundaries do not drive population structure in the study species. The data further show a significant change in spatial autocorrelation at about 20 km distance in both regions, indicating that dispersal is distance‐limited and reduced at distances above 20 km.